Comparative assessment of two traps for aphid monitoring in wheat under varying growth stages and environmental conditions - Abbas, Muneer; Javeed, Muhammad Tariq; Ahsan, Shahar Yar; Hussain, Niaz; Nadeem, Muhammad; Parveen, Zubeda; Ghaffar, Abdul; Abbas, Qaisar; Khaliq, Mudassar; Ali, Sajid (Journal of Pure and Applied Agriculture, 2025)
Yellow Moericke traps (YMT) and yellow sticky traps are critical components of integrated pest management (IPM), providing accurate data for population abundance and behavior. Two traps were assessed at various wheat growth stages to evaluate their effectiveness. Yellow Moericke Traps (YMT) consistently captured more aphids than Yellow Sticky Traps (YST) from the Booting to Ripening stages. Trap catches increased with rising temperatures peaking during the Heading stage. YMT consistently captured a higher number of aphids compared to YST across all nine sampling sites, with peak catches observed at the SW-12 site in both years. Aphid populations were notably higher in 2022, with YMT catches ranging from 10 to 401 and YST from 8 to 141. In 2023, a marked decline was observed, with YMT ranging from 5 to 320 and YST from 5 to 97. These facts make YMT a more reliable tool for monitoring populations trends. The correlation analysis during 2022-23 revealed a significant positive relationship between aphid catches and temperature for both trap types, with stronger correlations observed in 2023. In contrast, humidity showed a weak, no significant negative correlation with aphid catches in both years. No significant difference in correlation between the years and traps was found. The results show that Yellow Moericke Traps (YMT) consistently captured higher numbers of aphids (16,383) compared to Yellow Sticky Traps (YST) (7,098) during 2022-23, with significant differences observed (p < 0.05). Rhopalosiphum padi and Schizaphis graminum were the most abundant species, peaking during SW 03-09 and SW 05-13, respectively. YMT demonstrated greater efficiency, consistently capturing higher numbers across all aphid species and peak activity periods. This indicates higher efficacy in both attracting and capturing aphids. YMT proved to be a more dependable tool for monitoring aphid populations and tracking seasonal variations. Traps attracted thirteen species, with S. graminum, R. padi, S. avenae, and R. maidis were identified as major species.